I feel Lonely why do I feel lonely today? - Braddon, Amy; Day, Teresa; Flynn, Sonny (London Dorling Kindersley Limited, 2021)
Everybody feels lonely sometimes, it can make us feel sad and worried, learn about how loneliness feels, what happens inside our bodies, and all the things.. you can do to stop feeling lonely
Linguistic notions
Keywords: Board books; Emotions; Picture books